An Enthusiastic but Uncertain Welcome: Coverage of Risks, Benefits, and Social Contexts of CRISPR Technology in U.S. Agricultural News 2012-2022 - Lindsey Middleton; Anqi Shao; Ashley Cate; Jade Haugen; Nan Li (Journal of Applied Communications, 2024)
To foster the responsible development and governance of CRISPR, it is important to understand how agricultural communities perceive and discuss this technology. This study conducted a content analysis of 529 articles from 53 diverse agricultural news publications across sectors and U.S. regions between 2012 and 2022. We analyzed how CRISPR technology is depicted in terms of risk, benefit, social/policy context, quoted experts, and the mentioning of other biotechnologies. Our findings show that from the time that CRISPR was developed for agriculture over a decade ago, agricultural news has consistently reflected a pro-innovation stance, frequently describing its benefits as well as advantages over longer-standing biotechnologies. Industry representatives were quoted most frequently, followed by university scientists and political representatives, while producers and non-governmental groups were quoted least frequently. Technology-related risks (off-target effects, financial risks) were notably lacking, but CRISPR’s social context was covered more extensively, including uncertainties in regulation and consumer acceptance. We discussed the implications for agricultural news professionals, communicators, and future researchers, emphasizing the importance of fostering a more balanced discourse and ensuring informed decision-making within the agricultural sector.
Keywords: CRISPR gene editing; newspapers; content analysis; food; agriculture